Auger Electron Spectroscopy-A Review - Bhavyasri, K.; Sreshta, M.; Swethasri, R. (Asian Journal of Pharmaceutical Research and Development, 2019)
Auger electron spectroscopy (AES) is surface sensitive analytical technique mainly,it provides quantitative elemental and chemical state information from surfaces of solid materials.It utilizes a high current, finely focused electron beam as an excitation source.In AES,A sample is probed with electron beam with energy between 3 to 3o Kev which results in ejection of electron in core level, filled by an outer level electron with excess energy being used then, this excess energy used to emit an electron this, emitted electron is said as Auger electron. That result as function of auger electron energy. The resulting spectra is obtained used to determine the composition of samples. The Auger electron kinetic energies are characteristic of emitting atoms and the measurement of their energies is used to identify the elements variation of composition with depth can be determined by ion sputtering technique. Lastly,AES is applicable for detection of thin films, characterization of materials, metallurgy and corrosion science.